Cancer Cell‐Derived Exosomal miR‐500a‐3p Modulates Hepatic Stellate Cell Activation and the Immunosuppressive Microenvironment - Yu Zhang; Xin Li; Huiyan Chen; Jiawei Li; Xiaohuan Guo; Yilin Fang; Linjie Chen; Kaiqiang Li; Yi Zhang; Fei Kong; Aodong Chen; Jianxin Lyu; et al. (Advanced Science)
Abstract Hepatocellular carcinoma (HCC) mainly depends on liver fibrosis/cirrhosis, which is regulated by tumor cells and the tumor microenvironment (TME), and is a crucial factor in tumor progression. This study aimed to identify abnormally expressed miR‐500a‐3p in the hepatitis‐cirrhosis‐HCC pathway and explored the roles of miR‐500a‐3p in HCC progression. A clinical cohort of patients with HCC is studied retrospectively. Subsequently, the role of miR‐500a‐3p transported by HCC exosomes in hepatic stellate cell (HSC) activation, hepatoma growth and invasion, and immune cell differentiation is determined by in vitro and in vivo experiments. In clinical tissues, miR‐500a‐3p is significantly enriched in HCC and cirrhosis tissues, and co‐expression of the immune marker CD4 or PD‐L1 significantly correlates with low survival rates in patients. Extracellular miR‐500a‐3p is taken up by HSC and PBMC, which promotes the secretion of the cytokines TGF‐β1 and IL‐10, increases PD‐L1 expression in HSC, and stabilizes PD‐1 expression in PBMC to affect the TME. Moreover, miR‐500a‐3p is associated with CD4+ T‐cell exhaustion and Treg differentiation and is significantly associated with increased tumorigenicity in in situ mouse HCC models. Mechanistically, HCC‐derived exosomal miR‐500a‐3p directly influences SOCS2 to regulate the JAK3/STAT5A/STAT5B signaling pathway. MiR‐500a‐3p promotes the growth and migration of HCC through the SOCS2/JAK3/STAT5A/STAT5B axis.